Trifarotene alleviates skin photoaging injury by inhibition of JNK/c-Jun/MMPs - Fei Xuan; Yang Lele Zixin; Zhang Jingjing; Li Xiang; Pan Mengtian; Xu Guangchen; Zhang Cuixia; Liu Fei; Fang Weirong (Acta Pharmaceutica)
Long-term exposure to ultraviolet (UV) radiation induces skin photoaging, which manifests as oxidative stress, inflammation, and collagen degradation. Multiple approaches (topical or systemic retinoids, antioxidants, alpha-hydroxy acids, laser, surgery) are used in the treatment of photoaged skin, and the use of topical retinoids is currently a primary clinical treatment. Previous studies revealed that retinoic acid promotes keratinocyte proliferation and reduces melanin deposition and matrix metalloproteinase (MMP) secretion; it also causes potential allergic and inflammatory damage to the skin. This study aimed to investigate the therapeutic effects and mechanisms of trifarotene, a functional retinoic acid analog, on UV-irradiated photoaging ICR and BALB/c nude mice and UVB photodamaged human epidermal keratinocyte (HaCaT) cells by examining indicators such as collagen, oxidoreductase, and inflammatory factor presence through histochemical staining, Western blot, and ELISA. Results suggested that trifarotene significantly reduced UV-induced photoaging in mouse skin tissue, potentially by reducing oxidative stress damage and inflammatory factor release, and inhibiting melanin deposition and collagen degradation by downregulating MMP expression. Concentrations of malondialdehyde, tyrosinase, interleukin-6, interleukin- 12, and tumor necrosis factor-alpha in photoaged skin decreased, while SOD content in photodamaged HaCaT cells significantly increased. Trifarotene (3.3 μmol L–1) inhibited phosphorylated JNK and c-Jun expression both independently and collaboratively with the JNK activator anisomycin, demonstrating that trifarotene mitigates UV-induced collagen degradation and apoptosis through inhibition of the JNK/c-Jun/MMPs signaling pathway.